Hydration status affects mood state and pain sensation during ultra-endurance cycling - Moyen, N. E.; Ganio, M. S.; Wiersma, L. D.; Kavouras, S. A.; Gray, M.; McDermott, B. P.; Adams, J. D.; Binns, A. P.; Judelson, D. A.; McKenzie, A. L.; Johnson, E. C.; Muñoz, C. X.; et al. (Journal of Sports Sciences, 2015)
Laboratory-based studies indicate mild dehydration adversely affects mood. Although ultra-endurance events often result in mild to moderate dehydration, little research has evaluated whether the relationship between hydration status and mood state also exists in these arduous events. Therefore, the purpose of this study was to evaluate how hydration status affected mood state and perceptual measures during a 161 km ultra-endurance cycling event. One hundred and nineteen cyclists (103 males, 16 females; age = 46 ± 9 years; height = 175.4 ± 17.9 cm; mass = 82.8 ± 16.3 kg) from the 2011 and 2013 Hotter`N Hell events participated. Perceived exertion, Thermal, Thirst, and Pain sensations, Brunel Profile of Mood States, and urine specific gravity (USG) were measured pre- (~1 h before), mid- (~97 km), and post-ride. Participants were classified at each time point as dehydrated (USG = 1.022) or euhydrated (USG = 1.018). Independent of time point, dehydrated participants (USG = 1.027 ± 0.004) had decreased Vigour and increased Fatigue, Pain, Thirst, and Thermal sensations compared to euhydrated participants (USG = 1.012 ± 0.004; all P < 0.01). USG significantly correlated with Fatigue (r = 0.36), Vigour (r = -0.27), Thirst (r = 0.15), and Pain (r = 0.22; all P < 0.05). In conclusion, dehydrated participants had greater Fatigue and Pain than euhydrated participants. These findings indicate dehydration may adversely affect mood state and perceptual ratings during ultra-endurance cycling.